Electronic alteration of end-on phenyl groups of bis-triazolyl-silanes: electron-transport materials for blue phosphorescent OLEDs. Issue 22 (5th May 2016) - Yi, Seungjun; Bae, Woo-Ri; Kim, Jin-Hyoung; Lee, Ah-Rang; Kim, Woo-Young; Han, Won-Sik; Son, Ho-Jin; Kang, Sang Ook
Abstract : Electron transporting ability is controlled by alternating electronic properties of peryphery groups on silicon based oxadiazole moiety. Abstract : A series of modified bis(4-(4, 5-diphenyl-4 H -1, 2, 4-triazol-3-yl)phenyl)dimethylsilane (ST ), ST-CF3, ST-Me, ST- t Bu, andST-OMe, were designed and prepared by introducing electron-withdrawing groups or electron-donating groups at the 4-position of the end-on phenyl groups on the triazole ring. Systematic investigations of their thermal-, photophysical-, and electron-transporting (ET) properties were successfully carried out. Depending on the electronic characteristics of the substituents at the end-phenyl group on the triazole, their frontier orbital energy levels were controlled while maintaining energy band gaps. Low-temperature photoluminescence spectra indicate that all the preparedST moieties maintained high triplet energy states up to 2.85 eV owing to the suppression of electron delocalization by the silicon centre. The electron mobilities of all the compounds were investigated by fabricating electron only devices (EODs). The EOD ofST- t Bu showed significantly higher current density than the other analogs. Finally, the EL device utilizingST- t Bu as an electron transporting material in phosphorescent organic light-emitting diodes with bis[(4, 6-di-fluorophenyl)-pyridinate- N, C 2 ]picolinate (FIrpic) as a dopant showed an external quantum efficiency of 15.9%.